Multilevel assessment of chlorothalonil sediment toxicity to Latin American estuarine biota: Effects on biomarkers, reproduction and survival in different benthic organisms - Morais, Lucas Gonçalves [UNESP]; Gusso-Choueri, Paloma Kachel [UNESP]; Abreu, Fiamma Eugênia Lemos; Castro, Ítalo Braga; Abessa, Denis Moledo [UNESP]; Choueri, Rodrigo Brasil (Elsevier, 2023)
Chlorothalonil is an organochlorine compound that has long been used in agriculture. In recent years, this compound has been used as an antifouling booster biocide and its presence has been reported in marine coastal environments, especially in navigational areas. Although sediment can be a sink for chlorothalonil due to high affinity to fine particulate matter, toxicity studies with non-target marine and/or estuarine organisms is focused on waterborne exposure only. This study aimed to determine sediment-borne ecotoxicological effects of chlorothalonil on different benthic organisms of the Latin American biota using a integrative multilevel approach. Marine/estuarine organisms were exposed to sediments spiked with chlorothalonil (from 0 to 10.0 μg g−1) and effects at sub-individual (biochemical biomarkers in Anomalocardia flexuosa), individual (lethal effects to Tiburonella viscana and Artemia salina) and subpopulation levels (Nitokra sp. reproduction) were assessed. Increasing chlorothalonil concentrations in sediment caused increasing ecotoxicological effects in different levels of biological organisation, from biochemical to subpopulation levels. The highest exposure concentrations showed increased biomarkers of effects (lipid peroxidation and DNA damage in gills and/or digestive gland of A. flexuosa), lower fecundity and lower survival of the test organisms. GPx activity associated with LPO levels in the digestive gland suggested a response to the oxidant challenge provided by the biocide. At the lowest concentration (0.001 μg g−1), chlorothalonil detoxification mechanisms and defense against its oxidising action, involving GSH and glutathione-dependent enzymes (GST and GPx) were induced. At intermediate concentrations, there was a tendency of decreasing GSH levels, probably due to conjugation with chlorothalonil, which also affected the activities of the glutathione-dependent enzymes. At the highest tested concentration (10.0 μg g−1), chlorothalonil may have restimulated GSH synthesis in the gills of A. flexuosa, although the prooxidant activity has induced effects. This study contributes to assessing the environmental risk of chlorothalonil in sediment for non-target marine and estuarine organisms.
Keywords: Antifouling; Biocide; Ecotoxicology; Genotoxicity; Oxidative stress; Pollution